Polymorphism rs11867353 of Tyrosine Kinase Non-Receptor 1 (TNK1) Gene Is a Novel Genetic Marker for Alzheimer's Disease - Zeman, Tomáš; Balcar, Vladimir J; Cahová, Kamila; Janoutová, Jana; Janout, Vladimír; Lochman, Jan; Šerý, Omar (Molecular neurobiology, 2021)
Several single-nucleotide polymorphisms (SNPs) and rare variants of non-receptor tyrosine kinase 1 gene (TNK1) have been associated with Alzheimer's disease (AD). To date, none of the associations have proven to be of practical importance in predicting the risk of AD either because the evidence is not conclusive, or the risk alleles occur at very low frequency. In the present study, we are evaluating the associations between rs11867353 polymorphism of TNK1 gene and both AD and mild cognitive impairment (MCI) in a group of 1656 persons. While the association with AD was found to be highly statistically significant (p < 0.0001 for the risk genotype CC), no statistically significant association with MCI could be established. Possible explanation of the apparent discrepancy could be rapid progression of MCI to AD in persons with the CC genotype. Additional findings of the study are statistically significant associations of rs11867353 polymorphism with body mass index, body weight, and body height. The patients with AD and CC genotype had significantly lower values of body mass index and body weight compared with patients with other genotypes. The main outcome of the study is the finding of a previously never described association between the rs11867353 polymorphism of the TNK1 gene and AD. The rs11867353 polymorphism has a potential to become a significant genetic marker when predicting the risk of AD.
Keywords: Body Height; Female; Cognitive Dysfunction; ženské pohlaví; jednonukleotidový polymorfismus; lidé; Polymorphism, Single Nucleotide; fetální proteiny; genetická predispozice k nemoci; studie případů a kontrol; Genetic Predisposition to Disease; tělesná výška; Humans; tělesná hmotnost; genetické asociační studie; Male; Case-Control Studies; Aged; Alzheimer Disease; index tělesné hmotnosti; kognitivní dysfunkce; Fetal Proteins; Body Weight; Alzheimerova nemoc; senioři; genetické markery; mužské pohlaví; Protein-Tyrosine Kinases; Body Mass Index; Genetic Association Studies; tyrosinkinasy; Genetic Markers